Penerapan Pendidikan dan Pengembangan Karir Terhadap Kinerja Karyawan PT. Indomarco Sukabumi - Dewi Nur Anggraeni; Acep Samsudin; Erry Sunarya (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
This research aimed  to find out the association of education and training to ward employee performance. In this case, the associative method is used by researchers to find out and test whether there is an influence or not between educational variables and career development on employee performance. The population in the study of PT Indomarco Sukabumi, amounting to 80 people. For sampling using saturated sample research that is taken as a whole in the sample size of this study is 80 respondents. For data collection using research through observation, interviews, and questionnaires, doing documentation for data analysis techniques using this research is multiple linear regression. The data analysis technique used is multiple linear regression which is the result of research showing this educational variableand training on employee performance is positive and significant effect. Career development variable, employee career performance showed that the positive influence and significantly of employee performance.